2015
DOI: 10.1063/1.4937578
|View full text |Cite
|
Sign up to set email alerts
|

Colossal magnetoelectric effect in 3-1 multiferroic nanocomposites originating from ultrafine nanodomain structures

Abstract: We investigate colossal magnetoelectric coupling through interactions between ferroelectric and ferromagnetic nanodomains in 3-1 multiferroic BaTiO3/CoFe2O4 nanocomposites using a recent real-space phase field model based on the Landau-Ginzburg theory. A hierarchical ultrafine domain structure is characteristically formed in the nanocomposites, resulting in an extremely high density of domain walls, which causes polarization domains to be more susceptible to an external magnetic field via interfacial strain-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
8
0
7
Order By: Relevance
“…79 In the field of magnetoelectric heteorstructures, effective magnetoelectric coupling coefficients have been evaluated or predicted by effective medium theories, 80 87,88 and by phase-field simulations. [89][90][91][92][93][94] Note that phase-field method can predict the co-evolution of the microstructure (grain/domain structure) and its corresponding effective (linear 89,92 and nonlinear) 90,91,93,94 magnetoelectric coupling coefficients under externally applied fields. Notably, Ni et al 89 proposed a phase-field method to identify the optimum phase morphology in piezomagnetic-piezoelectric composites that lead to a maximum linear direct magnetoelectric coupling coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…79 In the field of magnetoelectric heteorstructures, effective magnetoelectric coupling coefficients have been evaluated or predicted by effective medium theories, 80 87,88 and by phase-field simulations. [89][90][91][92][93][94] Note that phase-field method can predict the co-evolution of the microstructure (grain/domain structure) and its corresponding effective (linear 89,92 and nonlinear) 90,91,93,94 magnetoelectric coupling coefficients under externally applied fields. Notably, Ni et al 89 proposed a phase-field method to identify the optimum phase morphology in piezomagnetic-piezoelectric composites that lead to a maximum linear direct magnetoelectric coupling coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…In ME VANs consisting of square-shaped CFO rods embedded in a BTO matrix, PF reveals that, while domain structures within rods are relatively simple, hierarchical ultrafine nanodomains are formed in the ferroelectric matrix (see Fig- ure 2c). 67 There is thus an extremely high density of domain walls that are susceptible to an externally applied H, leading to a high ME effect (see Figure 2d). 67 It has also been shown that, with maintaining the shapes and volume fraction of magnetic rods, the distribution of constituent phase, or the geometrical arrangement (square, honeycomb, and triangular arrays) of rods, strongly affects the final domain configuration (domain wall density) and thus the ME coefficient.…”
Section: Arrangement Aspect Ratio and Volume Fraction Effectsmentioning
confidence: 99%
“…67 There is thus an extremely high density of domain walls that are susceptible to an externally applied H, leading to a high ME effect (see Figure 2d). 67 It has also been shown that, with maintaining the shapes and volume fraction of magnetic rods, the distribution of constituent phase, or the geometrical arrangement (square, honeycomb, and triangular arrays) of rods, strongly affects the final domain configuration (domain wall density) and thus the ME coefficient. 67 PF can also be used to simulate ME VANs with periodically aligned cuboid-shaped CFO inclusions embedded in a BTO matrix.…”
Section: Arrangement Aspect Ratio and Volume Fraction Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40] On the other hand, modeling predicts complex domain evolution in composites. [41][42][43] PFM based investigation (direct ME effect) is expected to reveal a strong modulation of the local piezoresponse (i.e., polarization) as a function of the externally applied magnetic field [20][21][22][23][24][25][26][27][28] giving an indirect insight into the spatial distribution of the local magnetoelectro-mechanical interactions.…”
Section: Introductionmentioning
confidence: 99%